Sharia Crowdfunding As An Alternative Financing Solution The Capital City Of The Archipelago - moslem, habibah; KH, Hasbi Abdul Al-Wahhab; Al Arif, Muhammad Nur Rianto (Jurnal Ilmiah Ekonomi Islam, 2023)
The government plans to move the national capital from the Jakarta Special Capital Region to East Kalimantan, now known as the Nusantara Capital Region (IKN), in phases from the enactment of Law No. 3 in 2022. also plans to inaugurate the IKN on August 17, 2024 to coincide with the 79th anniversary of the Republic of Indonesia. However, this plan has problems in implementation as it requires a large budget of IDR 466 trillion with 20% funded by the state budget and 80% funded by the private sector. individuals, but so far no investor has made their investment in IKN. . This is due to a number of obstacles considered by large investors, such as high logistics costs and regulatory inconsistency. The purpose of this article is to analyze the difficulties encountered in funding the IKN project. Analytical techniques using descriptive qualitative methods with library research methods. The proposed results suggest an alternative source of financing using the Islamic crowdfunding model to attract investors.